Meningkatkan Keterampilan Bermain Alat Musik Tradisional: Sebuah Action Research di Sekolah Dasar - Hidayat, Restu Ahmad; Julia, Julia; Sunarya, Dede Tatang (Jurnal Pena Ilmiah, 2019)
The student interest of learning a traditional music instrument such as Saron and innovative media lacking in extracurricular learning traditional music instrument have an impact on the low skills of students. The purpose of this study is to improve the skills of students through the use of the VAM application as a medium for practicing and memorizing song notations in extracurricular of traditional music instrument. This study uses action research designs. The results in this study indicate students' skills in playing traditional musical instruments increased significantly after being given actions to apply VAM applications in extracurricular traditional music instrument. Students also like learning by using the VAM application in learning traditional music instrument. this is proven by a questionnaire or post-action survey, at the end of the study, according to them the VAM application is easy to play anytime and anywhere.